A Too Free Conduit? When the Flow of Men and Ideas Turned against Marie de Guise - Eric Durot (Etudes Epistémè)
The purpose of this essay is to describe the way in which the substantial circulation of men and ideas between France and Scotland ultimately turned against Marie de Guise and the kingdom of France in the years 1559 and 1560. In order to build a Franco-Scottish kingdom, an initial step towards a Franco-British Empire, the King of France, Henri II, helped increase this trans-Channel circulation of men and ideas. Henri II’s goal was to forge an alliance with both Scottish and English opponents of the Catholic Mary Tudor, particularly by supporting and employing notable Scottish Protestant figures. This policy failed after the Scots’ growing concerns about the “Frenchification” of their government encountered a new English political context in which a Protestant queen, Elizabeth Tudor, took the throne. The open conduit backfired against French ambitions and against the Regent of Scotland, Marie de Guise. The rebellion in Scotland that began in 1559 proved successful by 1560. It was a swift victory by the Protestant Lords that was partly due to the fact that they allied themselves with England after long benefiting from a highly tolerant French attitude. The English takeover of cross-Channel communications led to the isolation of the French army in Scotland and, with the Amboise conspiracy in 1560, to the opening of a second front in France. Significantly, a number of Protestant Scots officially serving the King of France were also double agents for the benefit of England.